(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This study describes mathematical study and relation between wind and earthquake and its effects on building as a whole with respect of Lateral force and Storey shear for different orientation of shear wall. The Effect of Storey drift and storey displacement is also estimated in study. Earthquake Lateral force, Storey Shear, Storey Drift and Storey Displacement are analyzed for Seismic zone factor II.